Influence of substrate heating on hole geometry and spatter area in femtosecond laser drilling of silicon - Jiao, Lishi (2014)
The objective of this research is to evaluate the effects of the hole geometry and the spatter area around the drilled hole by femtosecond laser deep drilling on silicon with various temperatures. Deep through holes were produced on single crystal silicon wafer femtosecond laser at elevated temperatures ranging from 300 K to 873 K in a step of 100 K. The laser drilling efficiency is increased by 56% when the temperature is elevated from 300 K to 873 K. The spatter area is found to continuously decrease with increasing substrate temperature. The reason for such changes is discussed based on the enhanced laser energy absorption at the elevated temperature.